Multiple nickel-sensitive targets elicit cardiac arrhythmia in isolated mouse hearts after pituitary adenylate cyclase-activating polypeptide-mediated chronotropy. (March 2017) - Tevoufouet, Etienne E.; Nembo, Erastus N.; Distler, Fabian; Neumaier, Felix; Hescheler, Jürgen; Nguemo, Filomain; Schneider, Toni
Graphical abstract: Abstract: The pituitary adenylate cyclase-activating polypeptide (PACAP)-27 modulates various biological processes, from the cellular level to function specification. However, the cardiac actions of this neuropeptide are still under intense studies. Using control (+|+) and mice lacking (−|−) either R-type (Cav 2.3) or T-type (Cav 3.2) Ca 2+ channels, we investigated the effects of PACAP-27 on cardiac activity of spontaneously beating isolated perfused hearts. Superfusion of PACAP-27 (20 nM) caused a significant increase of baseline heart frequency in Cav 2.3(+|+) (156.9 ± 10.8 to 239.4 ± 23.4 bpm; p < 0.01) and Cav 2.3(−|−) (190.3 ± 26.4 to 270.5 ± 25.8 bpm; p < 0.05) hearts. For Cav 3.2, the heart rate was significantly increased in Cav 3.2(−|−) (133.1 ± 8.5 bpm to 204.6 ± 27.9 bpm; p < 0.05) compared to Cav 3.2(+|+) hearts (185.7 ± 11.2 bpm to 209.3 ± 22.7 bpm). While the P wave duration and QTc interval were significantly increased in Cav 2.3(+|+) and Cav 2.3(−|−) hearts following PACAP-27 superfusion, there was no effect in Cav 3.2(+|+) and Cav 3.2(−|−) hearts. The positive chronotropic effects observed in the four study groups, as well as the effect on P wave duration and QTc interval were abolished in the presence of Ni 2+ (50 μM) and PACAP-27 (20 nM) in hearts from Cav 2.3(+|+) and Cav 2.3(−|−) mice. In addition to suppressing PACAP's response, Ni 2+ also induced conduction disturbances in investigated hearts. In conclusion, the most Ni 2+ -sensitive Ca 2+ channels (R- and T-type) may modulate the PACAP signaling cascade during cardiac excitation in isolated mouse hearts, albeit to a lesser extent than other Ni 2+ -sensitive targets.